2022
DOI: 10.3892/etm.2022.11263
|View full text |Cite
|
Sign up to set email alerts
|

Rare and unusual benign tumors of the sinonasal tract and pharynx: Case series and literature review

Abstract: There are a number of benign tumors of the nose and pharynx that are seldomly reported in literature but that can sometimes prove difficult to treat and extremely important for differential diagnosis. The present study presents cases of rare benign tumors localized in the pharynx, nasal and sinus cavities, as well as reviews of literature and historical references for each type of tumor. Unilateral nasal hemangioma in a 72-year-old male which, although not a rare pathology, raised problems due to auto-resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The sinonasal origin of the present tumor poses further difficulties not only for the diagnosis, with several benign and malignant mimickers existing in the area, but also concerning the accessibility to obtain a biopsy and perform a complete curative excision 24 . In the sinonasal cavity, the differential diagnoses include vascular, epithelial, and mesenchymal tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The sinonasal origin of the present tumor poses further difficulties not only for the diagnosis, with several benign and malignant mimickers existing in the area, but also concerning the accessibility to obtain a biopsy and perform a complete curative excision 24 . In the sinonasal cavity, the differential diagnoses include vascular, epithelial, and mesenchymal tumors.…”
Section: Discussionmentioning
confidence: 96%
“…Fortunately, a thorough morphologic examination and negative immunostaining for cytokeratins rule out the possibility of most epithelial lesions, including those of salivary gland origin, such as myoepitheliomas. 24 Glomangiopericytomas of the sinonasal type are distinguished based on the invariable expression of SMA and desmin, along with an abnormal nuclear localization of the beta-catenin protein. Another common vascular neoplasm in the area, nasal angiofibroma, can also make the diagnosis difficult in small biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal tumors may be seen as a typical proliferative lesion with tissue destruction or may mimic an inflammatory type in the early stages, showing polyps on endoscopy 1,2 . Some of these polyps are rare and unusual and require special attention in diagnostic and therapeutic management 3 …”
Section: Introductionmentioning
confidence: 99%
“…The anatomical regions represented by the nose, paranasal sinuses and the pharynx are frequently the place of occurrence for certain tumors (benign or malignant) of different histopathological origins. However, some of these tumors are very rare, unusual, requiring special attention in diagnosis, paraclinical investigations and therapeutic approach 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are authors who have suggested that haemangioma is actually a hamartoma that derives from the development of the mesoderm, which is endothelially differentiated and then it is vascularized and canalized 10 . Environmental and clinical risk factors are not always clear, sometimes they cannot be ruled out, so clinicians must take into account that genetic susceptibility is often intensified and complicated by environmental factors 2 .…”
Section: Introductionmentioning
confidence: 99%